Pemenuhan Kewajiban Adat dalam Tindak Pidana Kekerasan Seksual - Siregar, Elizabeth; Davega Prasna, Adeb; Rakhmawati, Dessy (PAMPAS: Journal of Criminal Law, 2025)
One of the progressiveness of the New Criminal Code that reflects harmonization and adaptation is the recognition of customary law values ​​by including sanctions for fulfilling local customary obligations as additional criminal penalties (Article 66 paragraph 1 letter f). Fulfillment of customary obligations correlates with Article 597 Paragraph 1: In relation to the meaning of "local customary obligations", the author tries to relate it to the customary law of Jambi City, which is connected to the crime of sexual violence. In general, sexual violence is regulated as an act prohibited by law, but are the acts regulated in the law also immediately regulated in detail as in customary law. In relation to the discussion of this topic, the next question is whether the crime of sexual violence can be given a sanction for fulfilling customary law. The purpose of this paper is to analyze the fulfillment of customary obligations (Jambi Customary Law) in the crime of sexual violence. The method used is empirical legal research. Fulfillment of customary obligations regulated in the New Criminal Code is a customary obligation based on local customary law rules. Regarding the crime of sexual violence, the Jambi customary institution has never received such a case. Regarding the criteria that can be classified as unlawful acts that exist in society, there are currently no rules. There are no restrictions on what acts are included in the group of these acts. If related to acts of sexual violence, acts that have not been regulated by law, but are considered reprehensible, can be grouped as unlawful acts that exist in society. To support the implementation of the New Criminal Code, guidelines for government and regional regulations and local customary courts are needed Abstrak Berlakunya KUHP Baru pada tahun 2026 nanti, memberikan ruang bagi hukum adat di Indonesia, untuk mengakselerasikan nilai hukum pidana adat dalam KUHP. Hal ini dibuktikan dalam KUHP Baru Pasal 66 Angka 1 huruf F, yang menyatakan salah satu sanksi pidana tambahan  adalah pemenuhan kewajiban adat setempat. Hal ini dimaknai bahwa dari pasal tersebut hukum pidana mengakui adanya penerapan sanksi pidana adat setempat (dalam topik penelitian khususnya adat Jambi). Urgensi dilakukannya penelitian ini adalah untuk menggali nilai hukum  adat Jambi yang dapat diterapkan sebagai sanksi pemenuhan kewajiban adat setempat dalam KUHP Baru. Tujuan penelitian ini, untuk mengetahui perbuatan pidana apa saja yang dapat diberikan sanksi pemenuhan kewajiban adat, relevansi penerapannya terhadap tindak pidana kekerasan seksual. Selain itu juga tujuan yang dicapai adalah, apa yang menjadi pedoman hakim dalam memberikan sanksi pemenuhan kewajiban adat, serta bagaimana persepsi hakim dan tokoh Lembaga Adat Melayu Jambi saat ini, terhadap sanksi pemenuhan kewajiban adat setempat.